2017
DOI: 10.1001/jamapsychiatry.2017.2702
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide for the Treatment of Antipsychotic Drug-Induced Weight Gain—Reply

Abstract: Dr Hasin reports serving as the principal investigator of a study on a measure of addiction to prescription opioids funded by InVentive Health Consulting, which combines support from 9 pharmaceutical companies. No other disclosures were reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Liraglutide has not been detected to cause drug interactions with antipsychotic medication used for schizophrenia (55), and in this study no change in CGI-S or SQLS was found during the intervention period (39) nor at the follow-up.…”
Section: Accepted Articlementioning
confidence: 47%
“…Liraglutide has not been detected to cause drug interactions with antipsychotic medication used for schizophrenia (55), and in this study no change in CGI-S or SQLS was found during the intervention period (39) nor at the follow-up.…”
Section: Accepted Articlementioning
confidence: 47%
“…However, little is known about the molecular mechanisms by which APs induce hyperphagia. Previous studies have relied on non-specific anti-obesity drugs that suppress basal feeding to reduce AP-induced weight gain (i.e., locaserin [ 30 ], orlistat [ 31 ], liraglutide [ 32 ], nizatidine [ 33 ] metformin [ 34 ]). While using anti-obesity drugs in combination with APs is clinically beneficial to offset weight gain, they do not shed light on the specific mechanisms underlying AP-induced hyperphagia.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have relied on non-specific anti-obesity drugs that suppress basal feeding to reduce AP-induced weight gain (i.e. locaserin 31 , orlistat 32 , liraglutide 33 , nizatidine 34 metformin 35 ). While using anti-obesity drugs in combination with APs is clinically beneficial to offset weight gain, they do not shed light on the specific mechanisms underlying AP-induced hyperphagia.…”
Section: Introductionmentioning
confidence: 99%